2020
DOI: 10.1177/0142723720941680
|View full text |Cite
|
Sign up to set email alerts
|

The unique role of verbal memory, vocabulary, concentration and self-efficacy in children’s listening comprehension in upper elementary grades

Abstract: Listening comprehension is important for daily communication and at school, yet relatively little is known about the variables contributing to listening comprehension, especially in the upper elementary years. The aim of this study was to explore whether vocabulary, verbal memory, but also self-efficacy and self-reported concentration contribute to listening comprehension. The authors assessed oral text comprehension, as well as the concurrent contributors vocabulary, verbal short- and long-term memory, self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 88 publications
0
8
0
2
Order By: Relevance
“…Vocabulary breadth, defined as the number of entries in the mental lexicon, has been the focus of research in both reading (Eason, Goldberg, Young, Geist, & Cutting, 2012; Muter, Hulme, Snowling, & Stevenson, 2004) and listening comprehension (Silva & Cain, 2015). More recent research has suggested that vocabulary depth, namely the extent of word‐related knowledge and the density of a speaker's semantic network (i.e., the number of links between words), plays a crucial role in comprehension (de Bree & Zee, 2020; Lepola et al. 2012).…”
Section: Background Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Vocabulary breadth, defined as the number of entries in the mental lexicon, has been the focus of research in both reading (Eason, Goldberg, Young, Geist, & Cutting, 2012; Muter, Hulme, Snowling, & Stevenson, 2004) and listening comprehension (Silva & Cain, 2015). More recent research has suggested that vocabulary depth, namely the extent of word‐related knowledge and the density of a speaker's semantic network (i.e., the number of links between words), plays a crucial role in comprehension (de Bree & Zee, 2020; Lepola et al. 2012).…”
Section: Background Literaturementioning
confidence: 99%
“…In the light of the literature on listening comprehension in monolingual children and the relative paucity of research on bilingual children, we investigated the following questions: How do foundational cognitive and language skills predict listening comprehension in bilingual children over time? On the basis of previous research (Kim, 2016) our hypothesis was that grammar (either syntactic and/or morphological knowledge) and inferential skills would have a direct effect on listening comprehension, over and above other cognitive and language skills. We also expected possible direct effects of vocabulary (either breadth or depth; de Bree & Zee, 2020; Silva & Cain, 2015) and memory (Kim, 2016). Is the growth of comprehension of literal information and of local and global inferences differentially affected by foundational cognitive and language skills? Our hypothesis was that different aspects of listening comprehension might grow differently over time and that different predictors might explain different comprehension abilities.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Listening comprehension is the first kind of speech activity a child acquires and is critical for language interactions and literacy acquisition, and it is significant for daily communication. 2,3,10,28 With the prevalence of PCs and smartphones and the growing use of apps, audiobooks have been advancing rapidly and are used increasingly commonly in blind children, which allows them to more easily obtain information by listening than Braille reading. For blind children, yet relatively little is known about the variables contributing to listening comprehension in primary school.…”
Section: Instructionmentioning
confidence: 99%